Non-linear elastic behavior of Ni-Fe-Ga(Co) shape memory alloy and Landau-energy landscape reconstruction. (1st February 2022) - Zoubková, Kristýna; Seiner, Hanuš; Sedlák, Petr; Villa, Elena; Tahara, Masaki; Hosoda, Hideki; Chernenko, Volodymyr
Graphical abstract: Abstract: We study the elastic behavior of single crystals of the Ni-Fe-Ga(Co) ferromagnetic shape memory alloy in a broad temperature range. Using tensile stress-strain measurements and ultrasonic characterization, we show that austenite and martensite phases of the given alloy exhibit strongly non-linear elastic responses, and we utilize the non-linear stress-strain data for constructing an energy function describing the observed behavior within the framework of the 4th-order Landau theory. The resulting energy landscape is shown to capture realistically several key features of the examined alloy, such as the existence of the critical point indicated by the extrapolation of the stress-strain data or the value and temperature dependence of the transformation strain. We provide explicit formulas for the energy landscape, using linear and quadratic approximations to express the temperature evolution of the Landau-energy parameters.